Refrigerant Selection for Cascade Water-to-water Heat Pump - Zhao Haibo; Yang Zhao (Zhileng xuebao)
Based on China National Standard-Number Designation and Safety Classification of Refrigerants, refrigerant for the cascade water-to-water heat pump were selected according to principles of environmental-friendly, safety and thermodynamic cycle performances. Different refrigerant combinations for high- and low-temperature cycles in the cascade heat pump were calculated and compared. Results show that combinations of R245fa/R134a, R245fa/R420A, R245fa/R413A, R245ca/R420A are better for the cascade heat pump. It also shows that, considering easy access and economy of refrigerants, R245fa/R134a combination will be a better choice.